2020
DOI: 10.15557/pipk.2020.0002
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity, measurement invariance and concurrent validity of Hospital Anxiety and Depression Scale in a sample of Polish undergraduate students

Abstract: With increasing levels of psychopathology observed in students in recent years, there is a clear need for short and valid tools for evaluating their psychological health. Hospital Anxiety and Depression Scale (HADS) is one of the most commonly used instruments measuring these constructs. The aim of this study was to examine the psychometric properties of the Polish version of HADS in a sample of undergraduate students. Material and methods: A total of 1,032 students took part in the study. The students' were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Seven items measure anxiety, and seven measure depression. The Polish version of the scale showed good validity and reliability in previous research (Czerwiński et al, 2020 ). In the present sample, the Cronbach’s alpha reliability coefficient was .74 for depression, and .85 for anxiety.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Seven items measure anxiety, and seven measure depression. The Polish version of the scale showed good validity and reliability in previous research (Czerwiński et al, 2020 ). In the present sample, the Cronbach’s alpha reliability coefficient was .74 for depression, and .85 for anxiety.…”
Section: Methodssupporting
confidence: 53%
“…Our study focused on the undergraduate students because they comprise almost half of the population age 19–24 in Poland (Główny Urząd Statystyczny, 2019 ) and previous studies showed that student populations are highly vulnerable to loneliness (American College Health Association, 2016 ). Polish studies showed high prevalence of depression and considerable hopelessness among university students (Czerwiński, Mackiewicz, Mytlewska, & Atroszko, 2020 ; Koryczan, Piotrowski, Roj, Czerwiński, & Atroszko, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Respondents provided answers on a four-point scale, with response categories from 0 to 3, the labels of which vary depending on the items. The scale showed good validity and reliability in previous research, including in screening studies with student samples [50,51]. The Cronbach's alpha reliability coefficients in the current sample were 0.74 for anxiety and 0.67 for depression.…”
Section: Anxiety and Depressionsupporting
confidence: 54%
“…The possible number of points for each question is in the range of 0–3, while the maximum number of points possible to obtain in each subscale is 21. α-Cronbach's coefficient for the subscale of depression symptoms is 0.82, and for anxiety 0.83 ( 36 ). In Polish studies, the Cronbach's α coefficient was 0.74 for depression and 0.85 for anxiety ( 37 ). In our study, the α-Cronbach's coefficient was 0.76; 95% CI 0.73–0.77 for depression and 0.84; 95% CI 0.82–0.86 for anxiety.…”
Section: Methodsmentioning
confidence: 99%